Leafhopper-Induced Activation of the Jasmonic Acid Response Benefits Salmonella enterica in a Flagellum-Dependent Manner - Cowles, Kimberly N.; Groves, Russell L.; Barak, Jeri D. (Frontiers in Microbiology, 2018)
Enteric human pathogens such as Salmonella enterica are typically studied in the context of their animal hosts, but it has become apparent that these bacteria spend a significant portion of their life cycle on plants. S. enterica survives the numerous stresses common to a plant niche, including defense responses, water and nutrient limitation, and exposure to UV irradiation leading to an increased potential for human disease. In fact, S. enterica is estimated to cause over one million cases of foodborne illness each year in the United States with 20% of those cases resulting from consumption of contaminated produce. Although S. enterica successfully persists in the plant environment, phytobacterial infection by Pectobacterium carotovorum or Xanthomonas spp. increases S. enterica survival and infrequently leads to growth on infected plants. The co-association of phytophagous insects, such as the Aster leafhopper, Macrosteles quadrilineatus, results in S. enterica populations that persist at higher levels for longer periods of time when compared to plants treated with S. enterica alone. We hypothesized that leafhoppers increase S. enterica persistence by altering the plant defense response to the benefit of the bacteria. Leafhopper infestation activated the jasmonic acid (JA) defense response while S. enterica colonization triggered the salicylic acid (SA) response. In tomato plants co-treated with S. enterica and leafhoppers, both JA- and SA-inducible genes were activated, suggesting that the presence of leafhoppers may affect the crosstalk that occurs between the two immune response pathways. To rule out the possibility that leafhoppers provide additional benefits to S. enterica, plants were treated with a chemical JA analog to activate the immune response in the absence of leafhoppers. Although bacterial populations continue to decline over time, analog treatment significantly increased bacterial persistence on the leaf surface. Bacterial mutant analysis determined that the bacterial flagellum, whether functional or not, was required for increased S. enterica survival after analog treatment. By investigating the interaction between this human pathogen, a common phytophagous insect, and their plant host, we hope to elucidate the mechanisms promoting S. enterica survival on plants and provide information to be used in the development of new food safety intervention strategies.